ChemInform Abstract: Palladium‐Catalyzed C—H Arylation of α, β‐Unsaturated Imines: Catalyst‐Controlled Synthesis of Enamine and Allylic Amine Derivatives. Issue 27 (16th June 2016) - Li, Minyan; Gonzalez‐Esguevillas, Maria; Berritt, Simon; Yang, Xiaodong; Bellomo, Ana; Walsh, Patrick J.
Abstract: A remarkable catalyst‐controlled chemo‐ and regioselective α‐ and γ‐arylation of azaallyl anion intermediates is developed.